التسوق الالكتروني في الدول النامية: دراسة مقارنة بين مصر والسعودية - Almobaireek, Wafa (مجلة العلوم الإدارية و الإقتصادية, 2013)
This study aims to determine the extent to which Egyptian and Saudi consumers comprehend the concept of e-shopping, and how often e-shopping is used in those nations. In addition, the study will explore benefits of, and difficulties to, participating in the e-shopping process. The study uses the descriptive method. The essential data has been collected using questionnaires filled out by a sample of final consumers in Egypt and Saudi Arabia. The sample size is 600 (300 from each country) and the response rate is 75%. The most important finding is that some Egyptian and Saudi consumers understand the concept of e-shopping, while others are confused between e-shopping and other electronic concepts. Compared to other usages of the internet and varieties of shopping, e-shopping is used very rarely by both Egyptian and Saudi consumers. There are a number of benefits, and some difficulties, that factor into Egyptian and Saudi consumers’ use of e-shopping. To address these, the study provides a list of recommendations .